Importancia del agroturismo en el Sector Rural Rcto. Pretoria del cantón Montalvo - Miranda Aguilar, Mercy Cristina (2020)
Agro tourism can be conceptualized in general terms as a tourist activity that allows the visitor to experience all those aspects linked to the customs and traditions of the countryside, in addition to being able to form part of the production process of the agricultural, forestry and artisanal crops that are found in a given community. In this case study, it offers some concepts about agro tourism, and comments on the main results of an analysis of the situation of agro tourism activity in the rural area of the Pretoria Precinct of Montalvo County. The results have been obtained, above all, through surveys to inhabitants of the area. Later, some conclusions are offered and, from these, a profile of recommendations is generated with the purpose of taking advantage of the potential of the agrarian systems for the integrated, endogenous and sustainable rural development of the area through agro tourism.